2016
DOI: 10.1080/14767058.2016.1265935
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome challenges in newborns with gastroschisis: A 6-year retrospective French study

Abstract: Future research should focus on decisions about delivery timing by incorporating risk of neonatal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This high proportion of deaths did not prompt the data safety management group to request an interruption of the trial at the first interim analysis, but it influenced our final decision to stop the study. Most studies report a rate of around 2–10% for prenatal death, which is in accordance with our own findings …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This high proportion of deaths did not prompt the data safety management group to request an interruption of the trial at the first interim analysis, but it influenced our final decision to stop the study. Most studies report a rate of around 2–10% for prenatal death, which is in accordance with our own findings …”
Section: Discussionsupporting
confidence: 92%
“…Another way of decreasing the inflammatory reaction is by using steroidal anti‐inflammatory compounds (dexamethasone), which have been used with success in various species . A recent study by Tosello et al also suggested that steroid administration reduces the duration of parenteral feeding in humans . In our study we decided to include dexamethasone injection in both arms because we considered that there was a risk of prematurity induced by the procedure, and an intrinsic risk of prematurity associated with gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs and eight observational cohort studies were included in the meta-analysis. 4,5,[11][12][13][14][15][16][17][18] All studies were published in English. Six of the included studies compared elective delivery at GA of 34 to 35 weeks for the infants with antenatally detected gastroschisis versus the control of expectant management, and four studies compared elective delivery at GA of 36 to 37 weeks versus the control of expectant management and delivery after GA of 36 to 37 for gastroschisis.…”
Section: Resultsmentioning
confidence: 99%
“…Group 1: Data was not sufficient for meta-analysis as only one study 15 presented date showing 0 death in elective delivery group and 2 (5.1%) deaths in control group.…”
Section: Mortalitymentioning
confidence: 99%
“…According to the literature, 17.4–55.5% of foetuses with GS have foetal growth restriction (FGR). Abnormal Doppler parameters in foetuses with gastroschisis are rarely seen, so FGR in this group may be related to protein and fluid loss through the exposed intestine rather than placental insufficiency [ 29 , 36 , 37 , 38 ]. In our study group, we observed a smaller number of foetuses with an FGR diagnosis.…”
Section: Discussionmentioning
confidence: 99%